Optimization of Biomimetic, Leukocyte-Mimicking Nanovesicles for Drug Delivery Against Colorectal Cancer Using a Design of Experiment Approach - Rampado, Riccardo; Biccari, Andrea; D’Angelo, Edoardo; Collino, Federica; Cricrì, Giulia; Caliceti, Paolo; Giordano, Federica; Taraballi, Francesca; Pucciarelli, Salvatore; Agostini, Marco (Frontiers in Bioengineering and Biotechnology, 2022)
The development of biomimetic nanoparticles (NPs) has revolutionized the concept of nanomedicine by offering a completely new set of biocompatible materials to formulate innovative drug delivery systems capable of imitating the behavior of cells. Specifically, the use of leukocyte-derived membrane proteins to functionalize nanovesicles (leukosomes) can enable their long circulation and target the inflamed endothelium present in many inflammatory pathologies and tumors, making them a promising and versatile drug delivery system. However, these studies did not elucidate the critical experimental parameters involved in leukosomes formulation. In the present study, we approached the preparation of leukosomes using a design of experiment (DoE) method to better understand the influence of experimental parameters on leukosomes features such as size, size distribution, and protein loading. We also validated this formulation technologically and tested its behavior in in vitro colorectal cancer (CRC) models, including CRC patient-derived tumor organoids (PDOs). We demonstrated leukosomes biocompatibility, endothelium adhesion capability, and tumor target in three-dimensional (3D) settings using CRC cell lines. Overall, our study offers a novel conceptual framework for biomimetic NPs using a DoE strategy and consolidates the high therapeutic potential of leukosomes as a viable drug delivery system for anti-inflammatory and antineoplastic applications.